Cardiovascular risk scores: qualitative study of how primary care practitioners understand and use them - Liew, Su May (Royal College of General Practitioners, 2013)
BACKGROUND: The National Institute for Health and Care Excellence guidelines and the Quality Outcomes Framework require practitioners to use cardiovascular risk scores in assessments for the primary prevention of cardiovascular disease. AIM: To explore GPs understanding and use of cardiovascular risk scores. DESIGN AND SETTING: Qualitative study with purposive maximum variation sampling of 20 GPs working in Oxfordshire, UK. METHOD: Thematic analysis of transcriptions of face-to-face interviews with participants undertaken by two individuals (one clinical, one non-clinical). RESULTS: GPs use cardiovascular risk scores primarily to guide treatment decisions by estimating the risk of a vascular event if the patient remains untreated. They expressed considerable uncertainty about how and whether to take account of existing drug treatment or other types of prior risk modification. They were also unclear about the choice between the older scores, based on the Framingham study, and newer scores, such as QRISK(®). There was substantial variation in opinion about whether scores could legitimately be used to illustrate to patients the change in risk as a result of treatment. The overall impression was of considerable confusion. CONCLUSION: The drive to estimate risk more precisely by qualifying guidance and promoting new scores based on partially-treated populations appears to have created unnecessary confusion for little obvious benefit. National guidance needs to be simplified, and, to be fit for purpose, better reflect the ways in which cardiovascular risk scores are currently used in general practice. Patients may be better served by simple advice to use a Framingham score and exercise more clinical judgement, explaining to patients the necessary imprecision of any individual estimate of risk.